253 Physical activity patterns in adolescents and young adults with intellectual and developmental disabilities. (April 2022) - Helsel, Brian C.; Ptomey, Lauren T.; Washburn, Richard A.; Sherman, Joseph; Rice, Anna; Foster, Rachel; Donnelly, Joseph E.
Abstract : OBJECTIVES/GOALS: Individuals with intellectual and developmental disabilities (IDD) have lower levels of moderate-to-vigorous physical activity (MVPA) and a greater risk for sedentary-related comorbidities compared to their typically developing peers. Understanding activity patterns may provide opportunities for targeted physical activity interventions. METHODS/STUDY POPULATION: Secondary analyses were performed on baseline accelerometer data pooled from 2 clinical trials and a pilot study in adolescents (11-17 years) and young adults (18-21 years) with IDD. MVPA was assessed using accelerometers worn on the non-dominant hip during waking hours over 7 consecutive days. Data were collected at 60 hertz and activity counts were aggregated over 60 second epochs. Wear time was determined with the Choi algorithm and MVPA was classified using the Troiano adult or Freedson age-specific child cut-points. Mixed effects linear regressions were used to determine the effects of day of the week, time of the day, and season on MVPA. Diagnosis, gender, and age were used as fixed effect covariates with random intercepts varying among the participants and days of observation within each participant. RESULTS/ANTICIPATED RESULTS: There were 231 individuals (15.6 ± 2.8 years, 51.5% female) who had IDD (36.8% Autism, 48.1% Down syndrome) with 22, 498 minutes of MVPA. Individuals with IDD wore the accelerometers an average of 592 ± 254 min./day and completed 13.5 ± 17.9 min./day of MVPA. Average MVPA was lowest in individuals with Autism (12.6 ± 11.4 min./day) and Down syndrome (13.2 ± 9.3 min./day) when compared to those with other IDDs (16.8 ± 10.8 min./day). Participation in MVPA was similar in males (13.4 ± 10.7 min./day) and females (13.7 ± 9.9 min./day). Mixed effects linear regressions showed that individuals participated in fewer minutes of MVPA on the weekend (β = -0.75, p < 0.001) and from 12-3 pm (reference) when compared to before 12 pm (β = 0.87, p < 0.001) and 3-7 pm (β = 0.66, p=0.007). No significant seasonal effects were found. DISCUSSION/SIGNIFICANCE: Individuals with IDD were significantly less active on the weekend, but they did participate in more minutes of MVPA in the morning and late afternoon/early evening. Physical activity interventions aiming to increase MVPA on the weekend and during the early afternoon may increase the number of weekly minutes of MVPA in individuals with IDD.